Phenotype and severity of asthma determines bronchial epithelial immune responses to a viral mimic. Issue 1 (28th July 2022) - Porsbjerg, Celeste; Nieto-Fontarigo, Juan Jose; Cerps, Samuel; Ramu, Sangheeta; Menzel, Mandy; Hvidtfeldt, Morten; Silberbrandt, Alexander; Frøssing, Laurits; Klein, Ditte; Sverrild, Asger; Uller, Lena
Background: Asthma is characterised by an aggravated immune response to respiratory viral infections. This phenomenon is a clinically well-recognised driver of acute exacerbations, but how different phenotypes of asthma respond immunologically to viruses is unclear. Objectives: To describe the association between different phenotypes and severity of asthma and bronchial epithelial immune responses to viral stimulation. Methods: In the Immunoreact study, healthy subjects (n=10) and 50 patients with asthma were included; 30 (60%) were atopic, and 34 (68%) were eosinophilic; 14 (28%) had severe asthma. All participants underwent bronchoscopy with collection of bronchial brushings. Bronchial epithelial cells (BECs) were expanded and stimulated with the viral replication mimic poly (I:C) (Toll-like receptor (TLR)3 agonist) in vitro . The expression of TLR3-induced pro-inflammatory and antiviral responses of BECs were analysed using reverse transcriptase quantitative PCR and multiplex ELISA and compared across asthma phenotypes and severity of disease. Results: Patients with atopic asthma had increased induction of interleukin (IL)-4, interferon (IFN)-β, IL-6, tumour necrosis factor-α, and IL-1β after poly (I:C) stimulation compared to non-atopic patients, whereas in patients with eosinophilic asthma only IL-6 and IL-8 induction was higher than in non-eosinophilic asthma. Patients with severe asthma displayed a decreased antiviral IFN-β, and increased expression of IL-8, most pronounced in atopic and eosinophilic asthmatics. Furthermore, induction of IL-33 in response to poly (I:C) was increased in severe atopic and in severe eosinophilic asthma, but thymic stromal lymphopoietin only in severe eosinophilic asthma. Conclusions: The bronchial epithelial immune response to a viral mimic stimulation differs between asthma phenotypes and severities, which may be important to consider when targeting novel asthma treatments. The airway epithelial pro-inflammatory and anti-viral response to a viral stimulus differs with the phenotype and severity of asthma, indicating differences in immune drivers of exacerbations https://bit.ly/3DhTVWw